MINAT BACA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU (Studi Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Angkatan 2019) - ", Iqbal; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Reading interest is one of the problems that occur by college students, because college students nowadays play more on gadgets than read. The low interest in reading in students is due to lack of reading time, lack of visits to libraries to borrow books or read books, and the lack of books owned by college students or lecturers who rarely give assignments, telling  college students to buy books to read so that students lack reading. The formulation of the problems discussed in this study were the factors that influenced the reading interest of FISIP Universitas Riau college students and how the reading interest of the  Universitas Riau FISIP college students. The purpose of this study was to determine the factors that affect students' reading interest and to determine the level of reading interest among students of the Faculty of Social and Political Sciences Universitas Riau. The theory used in this research is the structural functionalism theory of Talcon Parsons adaptation, goal, integration, and latent patent maintenance. Data analysis used a descriptive method with a quantitative approach, the data collection technique in this study was proportional random sampling, that is, the population has the same opportunity to be the sample. The sampling technique used the Slovin formula, while the respondents in this study were 91 college students. From the results of this study it can be concluded that the factors that influence the reading interest of FISIP Universitas Riau students with the high category are latent factors (norms) and the low ones are in the objective factors and the level of reading interest of FISIP students of Universitas Riau is categorized as low.   Keywords : Interest, Reading, College Student